Initial tree census for the Paint Rock Forest Dynamics Plot, Alabama, USA - Dawn Lemke; Luben Dimov; Bill Finch; Patience Knight; Helen Czech; Loretta Weninegar; Richard Condit (Ecology, 2026)
We present the initial woody stem census for the 20‐ha Paint Rock Forest Dynamics Plot in 2019–2021 in north Alabama, USA. Our objectives were to improve our understanding of the ecology of the forest ecosystem, provide hands‐on research experience to undergraduate students, create opportunities for collaboration with other disciplines, and monitor the dynamics of the forest. From its origin at the south corner (latitude: 34.769521°, longitude: −86.306079°), our plot is a rectangle of 400 m × 500 m, having its long side at 313° azimuth. The plot is in a mature mixed deciduous forest within the mountain district of the Cumberland Plateau physiographic region. It is within the Nature Conservancy Sharp Bingham Mountain Preserve (1600 ha). The Preserve is protected from broad anthropogenic disturbance, but allows limited hunting outside of the plot. The plot's climate is humid subtropical, with hot, humid summers and cool, wet winters. The plot is on a deeply dissected karst landscape with a sandstone cap overlaying several layers of limestone. The majority of the plot (95%) is limestone rockland rough soils that are well‐drained with a parent material of residuum weathered from limestone. The remainder of the plot (5%) is Huntington silt loam, which occurs in the floodplains and toe slopes. The variable geology and topography offer a broad range of water availability, from dry benches to moist bottomland sinks, with steep to moderate slopes in between. Elevation ranges from 226 to 323 m above sea level. A 20 m × 20 m grid was professionally surveyed and installed across the 20 ha. Using this grid, we mapped and inventoried all living stems of woody plants (excluding vines) with a diameter of at least 1 cm at breast height. Trees with multiple stems were defined as those with aboveground forks off the main trunk, below breast height, at an angle x – y coordinates. Our taxonomic nomenclature follows that of the PLANTS database online, the Flora of the Southeastern United States, and the Alabama Plant Atlas. The initial census enumerated 29,280 free‐standing living stems from 27,418 woody individuals, including 79 species from 35 families. Among those were three gymnosperm and 46 angiosperm canopy stature trees (species that could potentially reach the canopy as free‐standing trees), and 30 species of mid‐ or understory tree species and shrubs. Canopy stature tree species made up 74.5% of the stems. Dominant canopy trees include white oak ( Quercus alba ), yellow‐poplar ( Liriodendron tulipifera ), sugar maple ( Acer saccharum ), white ash ( Fraxinus americana ), southern shagbark hickory ( Carya carolinae‐septentrionalis ), and American beech ( Fagus grandifolia ). This data set can be freely used for non‐commercial purposes. We request that users of these data cite this data paper in all publications resulting from the use of this data set.

Predicting Population Consequences of an Epidemic of High Pathogenicity Avian Influenza on Southern Elephant Seals - Claudio Campagna; Richard Condit; Mariano Ferrari; Julieta Campagna; Elena Eder; Marcela Uhart; Ralph E. T. Vanstreels; Valeria Falabella; Mirtha N. Lewis (Marine Mammal Science, 2025)
The colony of southern elephant seals ( Mirounga leonina ) at Península Valdés (Argentina) grew by 0.9% from 2000 to 2022, reaching a population of 18,000 reproductive females. In 2023, an epidemic of the High Pathogenicity Avian Influenza H5N1 virus led to the death of almost all pups and an unknown number of adults. We tested five scenarios that included complete pup mortality along with varying levels of adult mortality and reduced fertility. Newborn mortality had the smallest impact on the future population due to high natural mortality. Consequences of pup deaths will not appear until 2027, when those lost pups would have first reproduced. Scenarios including mature female mortality had more severe and immediate consequences, with a reduction in the breeding population in 2024 predicted to match the flu death rate. It took about 10 years for the population to readjust to the 2022 age distribution. In scenarios including adult mortality, it will take decades for the population to return to the 2022 level. The 2023 epidemic may thus reverse the conservation status of a population previously having no threats to continued growth.

Putting seedlings on the map: Trade‐offs in demographic rates between ontogenetic size classes in five tropical forests - Stephan Kambach; Helge Bruelheide; Liza S. Comita; Richard Condit; S. Joseph Wright; Salomón Aguilar; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; Nancy C. Garwood; Stephen P. Hubbell; Pei‐Jen Luo; Margaret R. Metz; et al. (Ecology, 2025)
All species must partition resources among the processes that underly growth, survival, and reproduction. The resulting demographic trade‐offs constrain the range of viable life‐history strategies and are hypothesized to promote local coexistence. Tropical forests pose ideal systems to study demographic trade‐offs as they have a high diversity of coexisting tree species whose life‐history strategies tend to align along two orthogonal axes of variation: a growth–survival trade‐off that separates species with fast growth from species with high survival and a stature–recruitment trade‐off that separates species that achieve large stature from species with high recruitment. As these trade‐offs have typically been explored for trees ≥1 cm dbh, it is unclear how species' growth and survival during earliest seedling stages are related to the trade‐offs for trees ≥1 cm dbh. Here, we used principal components and correlation analyses to (1) determine the main demographic trade‐offs among seed‐to‐seedling transition rates and growth and survival rates from the seedling to overstory size classes of 1188 tree species from large‐scale forest dynamics plots in Panama, Puerto Rico, Ecuador, Taiwan, and Malaysia and (2) quantify the predictive power of maximum dbh, wood density, seed mass, and specific leaf area for species' position along these demographic trade‐off gradients. In four out of five forests, the growth–survival trade‐off was the most important demographic trade‐off and encompassed growth and survival of both seedlings and trees ≥1 cm dbh. The second most important trade‐off separated species with relatively fast growth and high survival at the seedling stage from species with relatively fast growth and high survival ≥1 cm dbh. The relationship between seed‐to‐seedling transition rates and these two trade‐off aces differed between sites. All four traits were significant predictors for species' position along the two trade‐off gradients, albeit with varying importance. We concluded that, after accounting for the species' position along the growth–survival trade‐off, tree species tend to trade off growth and survival at the seedling with later life stages. This ontogenetic trade‐off offers a mechanistic explanation for the stature–recruitment trade‐off that constitutes an additional ontogenetic dimension of life‐history variation in species‐rich ecosystems.

Physiological tipping points in the relationship between foraging success and lifetime fitness of a long‐lived mammal - Roxanne S. Beltran; Keith M. Hernandez; Richard Condit; Patrick W. Robinson; Daniel E. Crocker; Chandra Goetsch; A. Marm Kilpatrick; Daniel P. Costa (Ecology Letters, 2023)
Although anthropogenic change is often gradual, the impacts on animal populations may be precipitous if physiological processes create tipping points between energy gain, reproduction or survival. We use 25 years of behavioural, diet and demographic data from elephant seals to characterise their relationships with lifetime fitness. Survival and reproduction increased with mass gain during long foraging trips preceding the pupping seasons, and there was a threshold where individuals that gained an additional 4.8% of their body mass (26 kg, from 206 to 232 kg) increased lifetime reproductive success three‐fold (from 1.8 to 4.9 pups). This was due to a two‐fold increase in pupping probability (30% to 76%) and a 7% increase in reproductive lifespan (6.0 to 6.4 years). The sharp threshold between mass gain and reproduction may explain reproductive failure observed in many species and demonstrates how small, gradual reductions in prey from anthropogenic disturbance could have profound implications for animal populations.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Birth timing after the long feeding migration in northern elephant seals - Richard Condit; Roxanne S. Beltran; Patrick W. Robinson; Daniel E. Crocker; Daniel P. Costa (Marine Mammal Science, 2022)
Northern elephant seals migrate long distances from feeding grounds to raise pups during a brief period on breeding beaches. Because gestation sets a parturition date months in advance, timing of the arrival must be precise; an early arrival would waste foraging time, but a late arrival would cause parturition failure. We used satellite‐tracked animals to examine this timing, establishing arrival and birth dates in 106 migrating females and estimating how far they traveled in the days just before birth. Females arrived a mean of 5.5 days prior to birth (range 1–11, SD = 1.5), and females arriving later in the breeding season had 1.8‐day shorter prebirth intervals relative to early arrivers. There was no correlation between female body condition, nor female age, and the prebirth interval. The last 15 days prior to birth, animals traveled as far as 1,465 km. Those farthest from the colony traveled >100 km per day, three times faster than animals near the colony at the same time. Despite migrations covering several thousand kilometers while pregnant, female elephant seals were able to time their arrival within days. This allows them to maintain a precise annual birth cycle for many years consecutively.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Counting niches: Abundance‐by‐trait patterns reveal niche partitioning in a Neotropical forest - Rafael D’Andrea; John Guittar; James P. O’Dwyer; Hector Figueroa; S. J. Wright; Richard Condit; Annette Ostling (Ecology, 2020)
Tropical forests challenge us to understand biodiversity, as numerous seemingly similar species persist on only a handful of shared resources. Recent ecological theory posits that biodiversity is sustained by a combination of species differences reducing interspecific competition and species similarities increasing time to competitive exclusion. Together, these mechanisms counterintuitively predict that competing species should cluster by traits, in contrast with traditional expectations of trait overdispersion. Here, we show for the first time that trees in a tropical forest exhibit a clustering pattern. In a 50‐ha plot on Barro Colorado Island in Panama, species abundances exhibit clusters in two traits connected to light capture strategy, suggesting that competition for light structures community composition. Notably, we find four clusters by maximum height, quantitatively supporting the classical grouping of Neotropical woody plants into shrubs, understory, midstory, and canopy layers.

Testing for changes in biomass dynamics in large‐scale forest datasets - Ervan Rutishauser; Stuart J. Wright; Richard Condit; Stephen P. Hubbell; Stuart J. Davies; Helene C. Muller‐Landau (Global Change Biology, 2020)
Tropical forest responses to climate and atmospheric change are critical to the future of the global carbon budget. Recent studies have reported increases in estimated above‐ground biomass (EAGB) stocks, productivity, and mortality in old‐growth tropical forests. These increases could reflect a shift in forest functioning due to global change and/or long‐lasting recovery from past disturbance. We introduce a novel approach to disentangle the relative contributions of these mechanisms by decomposing changes in whole‐plot biomass fluxes into contributions from changes in the distribution of gap‐successional stages and changes in fluxes for a given stage. Using 30 years of forest dynamic data at Barro Colorado Island, Panama, we investigated temporal variation in EAGB fluxes as a function of initial EAGB (EAGB i ) in 10 × 10 m quadrats. Productivity and mortality fluxes both increased strongly with initial quadrat EAGB. The distribution of EAGB (and thus EAGB i ) across quadrats hardly varied over 30 years (and seven censuses). EAGB fluxes as a function of EAGB i varied largely and significantly among census intervals, with notably higher productivity in 1985–1990 associated with recovery from the 1982–1983 El Niño event. Variation in whole‐plot fluxes among census intervals was explained overwhelmingly by variation in fluxes as a function of EAGB i , with essentially no contribution from changes in EAGB i distributions. The high observed temporal variation in productivity and mortality suggests that this forest is very sensitive to climate variability. There was no consistent long‐term trend in productivity, mortality, or biomass in this forest over 30 years, although the temporal variability in productivity and mortality was so strong that it could well mask a substantial trend. Accurate prediction of future tropical forest carbon budgets will require accounting for disturbance‐recovery dynamics and understanding temporal variability in productivity and mortality.

Seed‐to‐seedling transitions exhibit distance‐dependent mortality but no strong spacing effects in a Neotropical forest - Philippe Marchand; Liza S. Comita; S. Joseph Wright; Richard Condit; Stephen P. Hubbell; Noelle G. Beckman (Ecology, 2020)
Patterns of seed dispersal and seed mortality influence the spatial structure of plant communities and the local coexistence of competing species. Most seeds are dispersed in proximity to the parent tree, where mortality is also expected to be the highest, because of competition with siblings or the attraction of natural enemies. Whereas distance‐dependent mortality in the seed‐to‐seedling transition was often observed in tropical forests, few studies have attempted to estimate the shape of the survival‐distance curves, which determines whether the peak of seedling establishment occurs away from the parent tree (Janzen–Connell pattern) or if the peak attenuates but remains at the parent location (Hubbell pattern). In this study, we inferred the probability density of seed dispersal and two stages of seedling establishment (new recruits, and seedlings 20 cm or taller) with distance for 24 tree species present in the 50‐ha Forest Dynamics Plot of Barro Colorado Island, Panama. Using data from seed traps, seedling survey quadrats, and tree‐census records spanning the 1988–2014 period, we fit hierarchical Bayesian models including parameters for tree fecundity, the shape of the dispersal kernel, and overdispersion of seed or seedling counts. We combined predictions from multiple dispersal kernels to obtain more robust inferences. We find that Hubbell patterns are the most common and Janzen–Connell patterns are very rare among those species; that distance‐dependent mortality may be stronger in the seed stage, in the early recruit stage, or comparable in both; and that species with larger seeds experience less overall mortality and less distance‐dependent mortality. Finally, we describe how this modeling approach could be extended at a community scale to include less abundant species.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Community‐level species’ correlated distribution can be scale‐independent and related to the evenness of abundance - Youhua Chen; Tsung‐Jen Shen; Richard Condit; Stephen P. Hubbell (Ecology, 2018)
The spatial distribution of species is not random; instead, individuals tend to gather, resulting in a non‐random pattern. Previous studies used the independent negative binomial distribution ( NBD ) to model the distributional aggregation of a single species, in which the independence of the distribution of individuals of a species in different quadrats had been assumed. This way of analyzing aggregation will result in the scale‐dependent estimation of the aggregation or shape parameter. However, because non‐random (and therefore non‐independent) distribution of individuals of a species in a finite area can be caused by either correlated or clumped distribution of individuals of a species between neighboring sites, an alternative model would assume that the distribution of individuals of a species over different sampling areas is multinomial. Here, we showed that, by assuming that regional species abundance followed a NBD while using a multinomial distribution to assign individuals of species in different non‐overlapped sampling quadrats that are from a partition of the entire region (quantifying positive correlation or synchrony), the estimation of the shape parameter in this probabilistic model, which is the negative multinomial distribution ( NMD ), was scale‐invariant (i.e., the estimated shape parameter is identical across different partitions of the study region). Accordingly, the estimation of the shape parameter was related to regional species distribution alone. This implied that, the shape parameter at the community level, using the NMD model, reflected the evenness of interspecific abundance. As a comparison, if the distribution of individuals of a single species followed independent NBD s as studied previously, the shape parameter would measure the evenness of intraspecific abundance (quantifying single‐species’ distributional aggregation). Moreover, our study highlighted the necessity for adjusting the model for the effects of unsampled species when studying community‐level distributional patterns. Collectively, as long as a target area is partitioned into non‐overlapping quadrats (no matter how their sizes vary), the proposed NMD model in this study, along with the independent NBD s model, can be jointly formulated as a framework to reconcile the scale‐dependent debate on the shape parameter, unifying the relationship between inter‐ or intraspecific abundance and distributional patterns.

Effects of biotic interactions on tropical tree performance depend on abiotic conditions - Robert Muscarella; Julie Messier; Richard Condit; Stephen P. Hubbell; Jens‐Christian Svenning (Ecology, 2018)
Predicting biotic responses to environmental change requires understanding the joint effects of abiotic conditions and biotic interactions on community dynamics. One major challenge is to separate the potentially confounding effects of abiotic environmental variation and local biotic interactions on individual performance. The stress gradient hypothesis ( SGH ) addresses this issue directly by predicting that the effects of biotic interactions on performance become more positive as the abiotic environment becomes more stressful. It is unclear, however, how the predictions of the SGH apply to plants of differing functional strategies in diverse communities. We asked (1) how the effect of crowding on performance (growth and survival) of trees varies across a precipitation gradient, and (2) how functional strategies (as measured by two key traits: wood density and leaf mass per area, LMA ) mediate average demographic rates and responses to crowding across the gradient. We built trait‐based neighborhood models of growth and survival across a regional precipitation gradient where increasing precipitation is associated with reduced abiotic stress. In total, our dataset comprised ~170,000 individual trees belonging to 252 species. The effect of crowding on tree performance varied across the gradient; crowding negatively affected growth across plots and positively affected survival in the wettest plot. Functional traits mediated average demographic rates across the gradient, but we did not find clear evidence that the strength of these responses depends on species’ traits. Our study lends support to the SGH and demonstrates how a trait‐based perspective can advance these concepts by linking the diversity of species interactions with functional variation across abiotic gradients.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Resolving the paradox of clumped seed dispersal: positive density and distance dependence in a bat‐dispersed species - Anna Sugiyama; Liza S. Comita; Takashi Masaki; Richard Condit; Stephen P. Hubbell (Ecology, 2018)
One of the hypothesized benefits of seed dispersal is to escape density‐ and distance‐responsive, host‐specific, natural enemies near maternal plants where conspecific seed and seedling densities are high. Such high conspecific neighbor densities typically result in lower offspring growth and survival (i.e., negative density‐dependent effects), yet many dispersal modes result in clumped seed distributions. New World leaf‐nosed bats transport fruits to their feeding roosts and deposit seeds, thereby creating high‐density seed/seedling patches beneath feeding roosts in heterospecific trees away from maternal trees, which seemingly nullifies a key benefit of seed dispersal. Such dispersal may still be adaptive if negative density‐dependent effects are reduced under feeding roosts or if the benefit of being dispersed away from maternal trees outweighs negative effects of conspecific seed/seedling density below roosts. We mapped the entire post‐germination population of a bat‐dispersed tree species Calophyllum longifolium (Calophyllaceae) in a 50‐ha plot on Barro Colorado Island, Panama in each of three successive years. We tested two hypotheses: (1) distance‐dependent effects are stronger than density‐dependent effects on seedling performance because seedlings far from conspecific adults are more likely to escape natural enemies even when at high densities and (2) negative density‐dependent effects will be reduced far from vs. near conspecific adults. Density and distance were naturally decoupled, as expected. However, in contrast to our expectation, we found positive density effects on seedling survival and density‐dependent effects did not differ with distance from conspecific adults. Both density and distance had positive effects on seedling survival when considered together, while only year had a significant effect on seedling growth. Thus, both being dispersed under bat feeding roosts and escaping the vicinity of conspecific adults were beneficial for C. longifolium seedling survival, supporting the directed dispersal and escape hypotheses, respectively. Despite resulting in high densities of conspecific seedlings, favorable habitat under bat feeding roosts and lack of negative density‐dependent effects appear to provide evolutionary advantages in C. longifolium .

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Beyond the fast–slow continuum: demographic dimensions structuring a tropical tree community - Nadja Rüger; Liza S. Comita; Richard Condit; Drew Purves; Benjamin Rosenbaum; Marco D. Visser; S.J Wright; Christian Wirth (Ecology Letters, 2018)
Life‐history theory posits that trade‐offs between demographic rates constrain the range of viable life‐history strategies. For coexisting tropical tree species, the best established demographic trade‐off is the growth‐survival trade‐off. However, we know surprisingly little about co‐variation of growth and survival with measures of reproduction. We analysed demographic rates from seed to adult of 282 co‐occurring tropical tree and shrub species, including measures of reproduction and accounting for ontogeny. Besides the well‐established fast–slow continuum, we identified a second major dimension of demographic variation: a trade‐off between recruitment and seedling performance vs. growth and survival of larger individuals (≥ 1 cm dbh) corresponding to a ‘stature–recruitment’ axis. The two demographic dimensions were almost perfectly aligned with two independent trait dimensions (shade tolerance and size). Our results complement recent analyses of plant life‐history variation at the global scale and reveal that demographic trade‐offs along multiple axes act to structure local communities.

Species–area relationships and biodiversity loss in fragmented landscapes - Ryan A. Chisholm; Felix Lim; Yi Shuen Yeoh; Wei Wei Seah; Richard Condit; James Rosindell (Ecology Letters, 2018)
To estimate species loss from habitat destruction, ecologists typically use species–area relationships, but this approach neglects the spatial pattern of habitat fragmentation. Here, we provide new, easily applied, analytical methods that place upper and lower bounds on immediate species loss at any spatial scale and for any spatial pattern of habitat loss. Our formulas are expressed in terms of what we name the ‘Preston function’, which describes triphasic species–area relationships for contiguous regions. We apply our method to case studies of deforestation and tropical tree species loss at three different scales: a 50 ha forest plot in Panama, the tropical city‐state of Singapore and the Brazilian Amazon. Our results show that immediate species loss is somewhat insensitive to fragmentation pattern at small scales but highly sensitive at larger scales: predicted species loss in the Amazon varies by a factor of 16 across different spatial structures of habitat loss.

Contrasting outcomes of species‐ and community‐level analyses of the temporal consistency of functional composition - Masatoshi Katabuchi; S. Joseph Wright; Nathan G. Swenson; Kenneth J. Feeley; Richard Condit; Stephen P. Hubbell; Stuart J. Davies (Ecology, 2017)
Multiple anthropogenic drivers affect every natural community, and there is broad interest in using functional traits to understand and predict the consequences for future biodiversity. There is, however, no consensus regarding the choice of analytical methods. We contrast species‐ and community‐level analyses of change in the functional composition for four traits related to drought tolerance using three decades of repeat censuses of trees in the 50‐ha Forest Dynamics Plot on Barro Colorado Island, Panama. Community trait distributions shifted significantly through time, which may indicate a shift toward more drought tolerant species. However, at the species level, changes in abundance were unrelated to trait values. To reconcile these seemingly contrasting results, we evaluated species‐specific contributions to the directional shifts observed at the community level. Abundance changes of just one to six of 312 species were responsible for the community‐level shifts observed for each trait. Our results demonstrate that directional changes in community‐level functional composition can result from idiosyncratic change in a few species rather than widespread community‐wide changes associated with functional traits. Future analyses of directional change in natural communities should combine community‐, species‐, and possibly individual‐level analyses to uncover relationships with function that can improve understanding and enable prediction.

Population size and migratory connectivity of humpback whales wintering in Las Perlas Archipelago, Panama - Hector M. Guzman; Richard Condit; Betzi Pérez‐Ortega; Juan J. Capella; Peter T. Stevick (Marine Mammal Science, 2015)
From 2003 to 2009, we surveyed Las Perlas Archipelago off the Pacific coast of Panama 53 times between the months of August and October to estimate abundance of humpback whales and to test for a migratory connection with populations from the southern hemisphere. We identified 295 individuals using photo‐identification of dorsal fins, including 58 calves, and the population estimate for a single season was 100–300 solitary adults plus 25–50 mothers with calves; the estimated population of animals across all seasons using a mark and recapture model was over 1,000. Eight of the 139 fluke identifications were matched to whales in photograph catalogues from the Antarctic Peninsula and a ninth was matched to a whale sighted in Chilean waters; four of these nine individuals have also been sighted in Colombia. We conclude that Panama (Las Perlas Archipelago in particular) is an important calving area for humpback whales in the Southern Hemisphere. These data should provide a foundation for monitoring of population change and to increase awareness in Panama about the need to manage vessel traffic and tourism related to the whales at Las Perlas.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Lifetime survival rates and senescence in northern elephant seals - Richard Condit; Joanne Reiter; Patricia A. Morris; Ryan Berger; Sarah G. Allen; Burney J. Le Boeuf (Marine Mammal Science, 2014)
The aim of this study was to extend 40 yr of prior demographic work on northern elephant seals ( Mirounga angustirostris ) at Año Nuevo, California, by including the oldest animals. We used a Bayesian mark‐recapture analysis to estimate lifelong survival and lifespan of a cohort of 372 weaned pups branded in 1985–1987 and resighted until 2008. Annual survival probability of females averaged 86.3%/yr at ages 5–16, then declined until age 21, the age of the oldest female. Male survival was lower, averaging 67.7%/yr from age 1 to age 15, the age of the oldest male. Northern elephant seal females in the expanding population at Año Nuevo live longer than southern elephant seal females ( M. leonina ) at colonies whose populations are declining. This comparison suggests that high survival of females is a key factor in population growth.

The founding of a southern elephant seal colony - Mariano A. Ferrari; Claudio Campagna; Richard Condit; Mirtha N. Lewis (Marine Mammal Science, 2013)
The only large mainland colony of southern elephant seals ( Mirounga leonina ) is on Península Valdés, at 42°S, in Argentine Patagonia. Censuses of pups have been carried out regularly there since 1970, and the population grew five‐fold by 2010. Here we use Bayesian modeling tools to make rigorous estimates of the rate of population growth, r , and to estimate survival and recruitment parameters that could account for the growth, incorporating observation error across different census methods. In the 1970s, r = 8%/yr, but has slowed to

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Functional traits explain light and size response of growth rates in tropical tree species - Nadja Rüger; Christian Wirth; S. Joseph Wright; Richard Condit (Ecology, 2012)
Relationships between functional traits and average or potential demographic rates have provided insight into the functional constraints and trade‐offs underlying life‐history strategies of tropical tree species. We have extended this framework by decomposing growth rates of ∼130 000 trees of 171 Neotropical tree species into intrinsic growth and the response of growth to light and size. We related these growth characteristics to multiple functional traits (wood density, adult stature, seed mass, leaf traits) in a hierarchical Bayesian model that accounted for measurement error and intraspecific variability of functional traits. Wood density was the most important trait determining all three growth characteristics. Intrinsic growth rates were additionally strongly related to adult stature, while all traits contributed to light response. Our analysis yielded a predictive model that allows estimation of growth characteristics for rare species on the basis of a few easily measurable morphological traits.

Patterns of Soil Bacteria and Canopy Community Structure Related to Tropical Peatland Development - Tiffany G. Troxler; Makoto Ikenaga; Leonard Scinto; Joseph N. Boyer; Richard Condit; Rolando Perez; George D. Gann; Daniel L. Childers (Wetlands, 2012)

Habitat specificity and diversity of tree species in an African wet tropical forest - George B. Chuyong; David Kenfack; Kyle E. Harms; Duncan W. Thomas; Richard Condit; Liza S. Comita (Plant Ecology, 2011)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

A general framework for the distance–decay of similarity in ecological communities - Hélène Morlon; George Chuyong; Richard Condit; Stephen Hubbell; David Kenfack; Duncan Thomas; Renato Valencia; Jessica L. Green (Ecology Letters, 2008)
Species spatial turnover, or β ‐diversity, induces a decay of community similarity with geographic distance known as the distance–decay relationship. Although this relationship is central to biodiversity and biogeography, its theoretical underpinnings remain poorly understood. Here, we develop a general framework to describe how the distance–decay relationship is influenced by population aggregation and the landscape‐scale species‐abundance distribution. We utilize this general framework and data from three tropical forests to show that rare species have a weak influence on distance–decay curves, and that overall similarity and rates of decay are primarily influenced by species abundances and population aggregation respectively. We illustrate the utility of the framework by deriving an exact analytical expression of the distance–decay relationship when population aggregation is characterized by the Poisson Cluster Process. Our study provides a foundation for understanding the distance–decay relationship, and for predicting and testing patterns of beta‐diversity under competing theories in ecology.

ESTIMATING POPULATION SIZE IN ASYNCHRONOUS AGGREGATIONS: A BAYESIAN APPROACH AND TEST WITH ELEPHANT SEAL CENSUSES - Richard Condit; Burney J. Le Boeuf; Patricia A. Morris; Marshall Sylvan (Marine Mammal Science, 2007)
Many organisms reproduce in temporary aggregations where estimates of colony size can be made by direct counts. When individuals are not synchronous, however, early breeders depart before the last arrive, so counts underestimate the total breeding population. We present a model describing a colony's census as a function of arrival, breeding tenure, and the correlation between them, and we use it to illustrate how variance in arrival and tenure affect the census. Counts of breeding female northern elephant seals ( Mirounga angustirostris ) from 1975 to 2007 were used to test the model. Four of the model's parameters—population size, mean and variance of arrival date, and the correlation between arrival date and breeding tenure—could be estimated from census data using a Bayesian approach; prior estimates of two other parameters—mean tenure and its variance—had to be used to avoid overparameterization. The model's predictions fit observed censuses well and produced reliable estimates of population size and arrival behavior, showing that the maximum census was 8%–16% below the total number of breeding females. This method could be used for estimating abundance in any asynchronous aggregation, given independent information on one of the defining distributions: arrival, tenure, or departure.

The effect of climatic gradients, topographic variation and species traits on the beta diversity of rain forest trees - Priya Davidar; B. Rajagopal; D. Mohandass; Jean‐Philippe Puyravaud; Richard Condit; S. J. Wright; E. G. Leigh (Global Ecology and Biogeography, 2007)
Aim We assessed the rates of turnover of tree species with distance (beta diversity) in wet forests of the Western Ghats (WG) complex of India to see whether climate, topographic variation or species traits influence beta diversity. Location The Western Ghats is a chain of mountains about 1600 km in length, running parallel to the western coast of the Indian Peninsula from above 8° N to almost 21° N latitude. Methods We used data from 60 small plot inventories concentrated in three regions: the southernmost part of the Western Ghats (SWG) (8°24′ to 9°37′ N), the Nilgiri Hills (11°12′ to 11°14′ N), and the central Western Ghats (CWG) (12°32′ to 14°51′ N). We used Sorensen's index (SI) to estimate the similarity in species composition between two plots and regressed SI against the logarithm of the distance between plots to assess beta diversity. A bootstrapping procedure provided confidence intervals for regression coefficients. To test for the effects of climate, we regressed seasonality differences between plots against SI for low‐elevation ( Results Among all three regions, beta diversity was highest along the latitudinal axis, and along the rainfall gradient in the Kogar region. Differences in seasonality between sites were strongly related to beta diversity along the north–south seasonality gradient and within the SWG. Within the three regions, beta diversity was highest in the region with the strongest rainfall gradient and lowest for the topographically heterogeneous SWG. Beta diversity did not differ between forest strata and dispersal modes. Main conclusions We conclude that climate, particularly seasonality, is probably the primary driver of beta diversity among rain forest trees of the Western Ghats complex.

Rarity and abundance in a diverse African forest - David Kenfack; Duncan W. Thomas; George Chuyong; Richard Condit (Biodiversity and Conservation, 2007)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Above‐ground biomass estimation in closed canopy Neotropical forests using lidar remote sensing: factors affecting the generality of relationships - Jason B. Drake; Robert G. Knox; Ralph O. Dubayah; David B. Clark; Richard Condit; J. Bryan Blair; Michelle Hofton (Global Ecology and Biogeography, 2003)
Aim Previous studies have developed strong, site‐specific relationships between canopy metrics from lidar (light detecting and ranging) remote sensing data and forest structural characteristics such as above‐ground biomass (AGBM), but the generality of these relationships is unknown. In this study, we examine the generality of relationships between lidar metrics and forest structural characteristics, including AGBM, from two study areas in Central America with different precipitation patterns. Location A series of tropical moist forest sites in Panama and a tropical wet forest in Costa Rica. Methods Canopy metrics (e.g. canopy height) were calculated from airborne lidar data. Basal area, mean stem diameter and AGBM were calculated from measurements taken as a part of ongoing forest dynamics studies in both areas. We examined the generality of relationship between lidar metrics and forest structure, and possible environmental effects (e.g. leaf phenology). Results We found that lidar metrics were strongly correlated ( R 2 : 0.65–0.92) with mean stem diameter, basal area and AGBM in both regions. We also show that the relationships differed between these regions. Deciduousness of canopy trees in the tropical moist forest area accounted for the differences in predictive equations for stem diameter and basal area. The relationships between lidar metrics and AGBM, however, remained significantly different between the two study areas even after adjusting for leaf drop. We attribute this to significant differences in the underlying allometric relationships between stem diameter and AGBM in tropical wet and moist forests. Conclusions Important forest structural characteristics can be estimated reliably across a variety of conditions sampled in these closed‐canopy tropical forests. Environmental factors such as drought deciduousness have an important influence on these relationships. Future efforts should continue to examine climatic factors that may influence the generality of the relationships between lidar metrics and forest structural characteristics and assess more rigorously the generality of field‐derived allometric relationships.

An Ecosystem Report on the Panama Canal: Monitoring the Status of the Forest Communities and the Watershed - Roberto Ibáñez; Richard Condit; George Angehr; Salomón Aguilar; Tomas GarcÍa; Raul MartÍnez; Amelia Sanjur; Robert Stallard; S. Joseph Wright; A. Stanley Rand; Stanley Heckadon (Environmental Monitoring and Assessment, 2002)

Ecological Implications of Changes in Drought Patterns: Shifts in Forest Composition in Panama - Richard Condit (Climatic Change, 1998)

Parental investment and the secondary sex ratio in northern elephant seals - Burney J. Le Bœuf; Richard Condit; Joanne Reiter (Behavioral Ecology and Sociobiology, 1989)